Manajemen Banquet Dalam Menangani Event Wedding di Hotel Pangeran Beach Kota Padang - Alby Alfaro (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
This research is motivated by the condition of banquet management in handling wedding events at Pangeran Beach Hotel, Padang City, this can be seen from the lack of planning before the wedding event. This research is a descriptive study with qualitative data. The types of data used are primary data and secondary data. Data collection techniques used were interview, observation, and documentation. 1) The hotel does not have any planning regarding Research, organizing tasks and responsibilities of the Hotel. 2) planning on event design is only carried out by consumers, 3) Planning in determining the time and place of the wedding is only planned by the consumer. 4) Planning regarding coordination has been well planned, organizing tasks and responsibilities has been going well. 5) Planning the evaluation after the wedding event has been well planned by each hotel department, organizing the duties and responsibilities of each leader has been well implemented, the actions of the leadership of each department have been carried out properly and supervision in conducting evaluations has been well done.